Empowering Local Communities Based on Traditional Wisdom and Cultural Ethics in the Digital Era to Support Sustainability in Brunei Darussalam - Surveyandini, Mayla; Uripi, Cahyaningtyas Ria; Arinastuti, Arinastuti (PT. Amirul Bangun Bangsa, 2025)
This report discusses a community engagement initiative focused on empowering local communities in Brunei Darussalam by integrating traditional wisdom, cultural ethics, and digital literacy. The program aims to strengthen sustainable practices, enhance socio-economic resilience, and preserve cultural heritage while preparing communities for the opportunities and challenges of the digital era. All service participants from 2 (two) countries, Indonesia and Brunei, taking locations in Kampong Ayer, Pasar Gadong and EnergyHub Dermaga Diraja Brunei Darussalam. The integration of traditional wisdom with modern digital skills proved effective in enhancing community resilience. Participants demonstrated a strong interest in preserving cultural identity while embracing technology for economic and educational benefits